2018
DOI: 10.1111/jfd.12811
|View full text |Cite
|
Sign up to set email alerts
|

A new strain of white spot syndrome virus affecting Litopenaeus vannamei in Indian shrimp farms

Abstract: White spot syndrome virus (WSSV)-infected shrimp samples collected from grow-out ponds located at Nellore, Andhra Pradesh, India, showed WSSV negative and positive by PCR using primer sets specific to ORF119 and VP28 gene of WSSV, respectively. This indicated the deletion of genetic fragments in the genome of WSSV. The WSSV isolate along with lab strain of WSSV was subjected to next-generation sequencing. The sequence analysis revealed a deletion of 13,170 bp at five positions in the genome of WSSV-NS (new str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Behera et al (2018) reported for the first time the occurrence of TiLV in Nile tilapia farms in India. Change in the genome of WSSV of shrimp was observed in L. vannamei after its introduction to Indian shrimp culture system (Sivakumar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Behera et al (2018) reported for the first time the occurrence of TiLV in Nile tilapia farms in India. Change in the genome of WSSV of shrimp was observed in L. vannamei after its introduction to Indian shrimp culture system (Sivakumar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They found substantial differences between the two time periods and also the two host species, with the later viruses showing large deletions compared to the earlier viruses. Major deletions of redundant genes have also been noted in other regions in recent years [18, 30, 52, 54], and the deletion sites reported for the newer Indian strains were among those reported for WSSV-AU [18, 51].…”
Section: Discussionmentioning
confidence: 95%
“…P. vannamei was introduced in 2001 from Taiwan [35], but not on a large commercial scale until circa 2009 [50]. Sivakumar et al (2018) [51] compared WSSV sequences in Indian prawns from both prior to and after the large-scale introduction of P. vannamei and the subsequent disease in P. vannamei . They found substantial differences between the two time periods and also the two host species, with the later viruses showing large deletions compared to the earlier viruses.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the culture of L. vannamei was found to be successful in the beginning but is now facing difficulties because of serious disease problems caused by EHP, IMNV and WSSV (Rajendran et al, ; Sahul Hameed et al, ; Santhoshkumar et al, ). Recently, a new strain of WSSV with a deletion of 13,170 bp at five positions in the genome of WSSV relative to WSSV‐TH was reported after the introduction of L. vannamei into Indian waters (Sivakumar et al, ). The new strain was found to be more virulent when compared to the old strain of WSSV, and our surveillance programme carried out since 2002 revealed the replacement of old strain of WSSV by the new strain of WSSV in Indian shrimp culture system (Sivakumar et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new strain of WSSV with a deletion of 13,170 bp at five positions in the genome of WSSV relative to WSSV‐TH was reported after the introduction of L. vannamei into Indian waters (Sivakumar et al, ). The new strain was found to be more virulent when compared to the old strain of WSSV, and our surveillance programme carried out since 2002 revealed the replacement of old strain of WSSV by the new strain of WSSV in Indian shrimp culture system (Sivakumar et al, ).…”
Section: Discussionmentioning
confidence: 99%